2011
DOI: 10.1152/ajpheart.01007.2010
|View full text |Cite
|
Sign up to set email alerts
|

Glucan phosphate attenuates myocardial HMGB1 translocation in severe sepsis through inhibiting NF-κB activation

Abstract: phosphate attenuates myocardial HMGB1 translocation in severe sepsis through inhibiting NF-B activation. Am J Physiol Heart Circ Physiol 301: H848 -H855, 2011. First published June 3, 2011 doi:10.1152/ajpheart.01007.2010.-Myocardial dysfunction is a major consequence of septic shock and contributes to the high mortality of sepsis. High-mobility group box 1 (HMGB1) serves as a late mediator of lethality in sepsis. We have reported that glucan phosphate (GP) attenuates cardiac dysfunction and increases survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Viable cardiomyocytes may also actively secrete HMGB1 under stresses, such as the stimulation of LPS (Xu et al, 2010), though the secretory mechanism remains unclear. Translocation of HBMG1 from nuclei to cytosol was observed as well in stressed cardiomyocytes (Funayama et al, 2013; Ha et al, 2011). …”
Section: Damps Generated By Ischemic Cardiomyocytesmentioning
confidence: 87%
“…Viable cardiomyocytes may also actively secrete HMGB1 under stresses, such as the stimulation of LPS (Xu et al, 2010), though the secretory mechanism remains unclear. Translocation of HBMG1 from nuclei to cytosol was observed as well in stressed cardiomyocytes (Funayama et al, 2013; Ha et al, 2011). …”
Section: Damps Generated By Ischemic Cardiomyocytesmentioning
confidence: 87%
“…It has been reported that LPS-induced activation of NF-kB plays a pivotal role in HMGB1 release from cultured macrophages (34). The inhibition of NF-kB activation with an adenovirus-expressing IkBa mutation can attenuate HMGB1 translocation in cultured cells, as well as in a cecal ligation and puncture-induced animal model of sepsis (66). In addition, inhibitors of IKKa and IKKb have been shown to inhibit HMGB1-induced chemotaxis (67).…”
Section: Ea Inhibits Hmgb1 Release From Hyperoxia-exposed Macrophagesmentioning
confidence: 99%
“…The high mobility group protein (HMG)B1, a nuclear protein secreted by immune cells, such as macrophages and dendritic cells, is released into extracellular space, triggering inflammatory immune response, tumor metastasis and autoimmune disease. Extracellular HMGB1 interacts with a multi ligand-receptor for advanced glycation end products (RAGE) leading to the activation of nuclear factor (NF)jB proinflammatory signaling, thereby triggering a variety of inflammatory cytokines such as interleukin (IL)-1b, tumor necrosis factor (TNF)a, IL-4, IL-6 and interferon (IFN)c [5]. Moreover, the elevated levels of cytokines can further induce NFjB activation and thereby worsening the disease condition.…”
Section: Introductionmentioning
confidence: 99%